Ghana: Business perspectives - Invisible barriers to trade - International Trade Centre (ITC) (International Trade Centre (ITC), 2024)
This report examines the experiences of Ghanaian exporters and importers with trade regulations and related procedural obstacles – highlighting their concerns and the challenges they face. A survey of 960 traders on non-tariff measures found that almost half of exporters in Ghana encounter obstacles. This finding underscores the importance of the solutions proposed in the country’s National Export Development Strategy. The report finds that tackling foreign and domestic trade obstacles such as conformity assessment requirements, export inspections and customs clearance procedures could help Ghana boost its annual exports by up to $4.3 billion by 2025.

Plataformas de cuidados a mayores - Egea, Mercedes Navarro (Comares, 2024)
La esperanza de vida en nuestro país es una de las más altas del mundo. Se estima que en treinta años la tasa de dependencia de personas mayores con necesidades de cuidados en la UE alcanzará el sesenta por ciento.Este estudio aborda las cuestiones jurídico-tributarias que plantean las "plataformas digitales de cuidados" que operan en el ámbito nacional y que tienen por destinatarios a los mayores dependientes.Estas fórmulas empresariales, además del potencial que tienen para la generación de empleo y la innovación, contribuyen a mejorar la calidad del envejecimiento, pues la oferta de servicios (cuidados de larga duración, por períodos cortos o por horas) se adapta con mayor flexibilidad a las necesidades individuales de los mayores, preservando su independencia y autonomía en todo el ciclo de la vejez. Unos cuidados que han de ser de calidad, asequibles y accesibles.Interesa, por tanto, adentrarse en los aspectos más significativos de lo que podría ser una fiscalidad de plataformas, focalizada en aquellas que actúan como intermediarias conectando a vendedores o prestadores de servicios con usuarios, y que comprende medidas concretas en el IS y el IVA, así como nuevas obligaciones de suministro de información (DAC 7). En esta categoría de plataformas se reconocen la mayoría de las que operan en el ámbito de los cuidados. Y, puesto que se trata de un sector empresarial en crecimiento, presenta especial interés conocer en qué medida se pueden aprovechar las medidas fiscales introducidas para el fomento de las empresas emergentes (startups), así como para la atracción de inversión privada y la captación de talento extranjero.
https://orcid.org/0000-0001-7441-209X
Keywords: cuidadados; jurídico; mayores; plataformas; tributario

The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On - Heyns, Christof; Viljoen, Frans Jacobus; Murray, Rachel (Brill, 2024)
This collection of chapters tracks and explains the impact of the nine core United Nations human rights treaties in 20 selected countries, four from each of the five UN regions. Researchers based in each of these countries were responsible for the chapters, in which they assess the influence of the treaties and treaty body recommendations on legislation, policies, court decisions and practices. By covering the 20 years between July 1999 and June 2019, this book updates a study done 20 years ago.
PDF: https://brill.com/downloadpdf/edcollbook-oa/title/38945.pdf
Keywords: Comparative Social Sciences; Human Rights; Human Rights and Humanitarian Law; Humanitarian Law; International Law; International Law: Regional Perspectives

Loi type de la CNUDCI sur l'utilisation et la reconnaissance internationale de la gestion de l'identité et des services de confiance - United Nations Commission on International Trade Law (United Nations, 2024)

Uniform Law: Legal Responses to Globalisation - Basedow, Jürgen; Max-Planck-Institut für Ausländisches und Internationales Privatrecht (Hamburg, Germany) (Mohr Siebeck, 2024)
International conference proceedings
Keywords: COMMERCIAL LAW; Economic Analysis; PRIVATE INTERNATIONAL LAW; Uniform law

Climate Litigation and Justice in Africa - Bouwer, Kim; Etemire, Uzuazo; Field, Tracy-Lynn; Jegede, Ademola Oluborode (Bristol University Press, 2024)
This volume brings together an international team of contributors to provide a much-needed examination of climate litigation in Africa. The book outlines how climate litigation in Africa is distinct as well as pinpointing where it connects with the global conversation. Chapters engage with crucial themes such as human rights approaches to climate governance, corporate liability and the role of gender in climate litigation.
Keywords: Africa; Climate adjudication; Climate governance; Climate justice; Climate litigation

Arbitration rules: In force as from 15 January 2024 - Cairo Regional Centre for International Commercial Arbitration (CRCICA, 2024)

Règlement d'arbitrage : En vigueur à compter du 15 janvier 2024 - Centre régional du Caire pour l’arbitrage commercial international (CRCICA, 2024)

COFOLA 2024: Sborník příspěvků mladých právníků, doktorandů a právních vědců. Část 1, Daňové právo v proměnách času - Czudek, Damian (Masarykova Univerzita, 2024)
Sborník příspěvků zabývajících se aplikací a interpretací daňového práva, tvorby daňového práva ve smyslu jeho stability a předvídatelnosti, jak z pohledu daňových subjektů (zejména podnikatelů, ale i fyzických osob nepodnikatelů, ale také státu a jemu podřízených organizací (z pohledu předvídatelnosti příjmů do veřejných rozpočtů a stability veřejných financí).
Keywords: Droit fiscal; E-knihy; Elektronické knihy; Fiscalité; Knihy; Tax law; Čítárna

Rechtsformneuschöpfungen im in- und ausländischen Gesellschaftsrecht - Fleischer, Holger (Mohr Siebeck, 2024)
Gesellschaftsformen bilden die Essenz des Gesellschaftsrechts. Der vorliegende Band untersucht, welche Bereicherungen das Rechtsformentableau in jüngerer Zeit erfahren hat. Als Untersuchungsgegenstand dienen ihm rund 20 ausgewählte Rechtsformneuschöpfungen aus dem In- und Ausland, deren Entstehen und Entwicklung im Einzelnen aufbereitet werden. Wichtige Leitfragen lauten: Wann und warum haben Reformgesetzgeber neue Gesellschaftsformen eingeführt? Von wem stammte die Anregung zu ihrer Einführung? In welcher Hinsicht unterscheiden sie sich von den traditionellen gesellschaftsrechtlichen Gussformen? Wie haben sie sich seither im nationalen und internationalen Rechtsformenwettbewerb behauptet? Durch diese akribischen Einzelstudien entsteht ein facettenreiches Bild des Ideenreichtums in- und ausländischer Reformgesetzgeber mitsamt ihren Wegbereitern aus Unternehmenspraxis, Anwaltschaft, Notariat, Rechtspolitik und Rechtswissenschaft.
Keywords: Commercial law; Comparative law; Conflict of laws

COFOLA 2024: Sborník příspěvků mladých právníků, doktorandů a právních vědců. Část 2, Výzvy současné sociální politiky - Komendová, Jana; Smejkal, Michal; Tomášková, Eva; Janovec, Michal (Masarykova Univerzita, 2024)
Bezprostřední návaznost pracovněprávních vztahů při posuzování nároku na dovolenou Sociální pojištění a dohoda o provedení práce dle konsolidačního balíčku Implementuje česká právní úprava dostatečně požadavky práva evropské unie na institut zkušební doby? Výzvy sociálnej politiky v kontexte dane z nehnuteľností Lege artis v ohrožení? Výpověď bez udání důvodu aneb jak zvýšit flexibilitu českého pracovního trhu Slovenská právna úprava ochrany oznamovateľov protispoločenskej činnosti z pohľadu rovnakého zaobchádzania v zamestnaní Rovné odměňování zaměstnanců ve skupině společností pohledem českého a evropského práva Výpověď bez udání důvodu jako hybatel pracovního trhu? Prioritizácia manželstva v práve sociálneho zabezpečenia Jak oběti domácího násilí propadávají systémem sociálního zabezpečení Sociální fondy: Co přinášejí zaměstnancům vysokých škol? Revize sociálních dávek Nesezdané soužití – přehlížená sociální realita?
Keywords: Agreement on Work Activity; Agreement on Work Performance; Directive; E-knihy; Elektronické knihy; Immediate Continuity; Knihy; Leave; Čítárna

COFOLA 2024: Sborník příspěvků mladých právníků, doktorandů a právních vědců. Část 5, Dopravní a přepravní právo v mezinárodním a evropském rozměru - Křepelka, Filip; Richterová, Anna (Masarykova Univerzita, 2024)
Problematika kontrolního vážení v České republice Trestání přestupků v dopravě v evropském rozměru Zajištění dostatečné dopravní obslužnosti Elektromobily jako údajné bezpečnostní riziko v parkovacích domech. Má právo nějak reagovat? AI v oblasti silniční dopravy
Keywords: E-knihy; Elektronické knihy; Knihy; Čítárna

État de la situation sur les impacts sociétaux de l'intelligence artificielle et du numérique - 2024 - Obvia; Langlois, Lyse (Observatoire international sur les impacts sociétaux de l'IA et du numérique, 2024)
L'État de la situation sur les impacts sociétaux de l'intelligence artificielle et du numérique fait état des connaissances actuelles sur les impacts sociétaux de l'IA et du numérique, structurées autour des sept axes de recherche de l'Obvia : santé, éducation, travail et emploi, éthique et gouvernance, droit, arts et médias, et transition socio-écologique. Hypertrucages, désinformation, empreinte environnementale, droit d'auteur, évolution des conditions de travail… Le document recense les grandes questions de recherche soulevées par le déploiement progressif de ces nouvelles technologies, auxquelles viennent s'ajouter des cas d'usages et de pistes d'action. Il s'impose ainsi comme un outil complet et indispensable pour accompagner la prise de décision dans tous les secteurs bouleversés par ces changements.

The Rotterdam Rules Convention: United Nations Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea 2008 - Laurijssen, Peter (CMI, 2024)
Keywords: MARITIME LAW; UN Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea (2008)

Property in goods and the CISG - Maier-Lohmann, Till (Fachmedien Recht und Wirtschaft, dfv Mediengruppe, 2024)
Keywords: CONTRACTS; INTERNATIONAL SALE OF GOODS; UN Convention on Contracts for the International Sale of Goods (1980)

Derecho penal económico y de la empresa - Mata Barranco, Norberto J. de la; Dopico Gómez-Aller, Jacobo; Lascuraín Sánchez, Juan Antonio; Nieto Martín, Adán (Dykinson, 2024)

Jus Mundi Arbitration Review - Mistelis, Loukas; Fan, Kun (Jus Mundi, 2024)
Articles The Seven Cardinal Sins of Investment Dispute Settlement Investment Arbitration in the New Era: Engine or Obstacle in the Fight Against Climate Change? The UNIDROIT Principles as a Tool for the Internationalisation of Contracts by Arbitral Tribunals AI: The Modern Tribunal Assistant – Impact on Enforceability of Arbitral Awards under the New York Convention Automation & Augmentation: Artificial Intelligence in International Arbitration The IBA Guidelines on Conflicts of Interest in International Arbitration 2024 CIETAC: Overview of Dispute Resolution in the Digital Environment in China Swiss Supreme Court rejects CJEU’s Komstroy ruling Romania’s Supreme Court Decides that Associations and Foundations Based in Romania Can Only Set Up Arbitral Institutions if Authorized by Law Book Review – On Arbitration: V. V. Veeder QC, Selected Writings and Contributions to the Development of Law (Wordsworth & Veeder (eds), OUP 2023) Book Review – Investment Arbitration and Climate Change (Ipp & Magnusson (eds), Kluwer 2024)

Les contrats dans le secteur de l'édition : Guide à l'intention des auteurs et des éditeurs - Organisation mondiale de la Propriété intellectuelle (OMPI, 2024)
Keywords: Contrat d'édition; Droits d'auteur; Editeur; Edition

COFOLA 2024: Sborník příspěvků mladých právníků, doktorandů a právních vědců.. Část 8, Regulace, dohled a inovace na finančních trzích a v bankovním sektoru - Schweigl, Johan; Holubářová, Nikol (Masarykova Univerzita, 2024)
- Právní aspekty zavedení Centrální bankovní digitální měny (CBDC) v Evropě: výzvy a; - Novinky ve světě fintech; - Riziko praní špinavých peněz v kryptoprostoru; - Povolenie na poskytovanie služieb kryptoaktív podľa nariadenia MiCA – vybrané regulačné aspekty v podmienkach Slovenskej republiky; - Nekalé obchodní praktiky a nekalosoutěžní jednání v bankovním marketingu; - Finančné inovácie ako determinant súčasnej a anticipovanej regulácie na finančnom trhu v kontexte neoprávneného podnikania; Outsourcing marketingových aktivit v bankovním sektoru; Několik poznámek k dlouhodobému investičnímu produktu.

COFOLA 2024: Sborník příspěvků mladých právníků, doktorandů a právních vědců. Část 3, Aktuální otázky náhrady škody - Schweigl, Johan; Holubářová, Nikol; Janovec, Michal (Masarykova Univerzita, 2024)
Sborník příspěvků z konference. OBSAH - Kdo odpovídá za škodu způsobenou zvířetem? Otázka odpovědnosti a náhrady škody ve vztahu k živočišné říši - Náhrada nemajetkové újmy na zdraví: smíření s Metodikou, návrat k prováděcím předpisům nebo třetí cesta? - Náhrada škody v případech věcí, které jsou předmětem zvláštní obliby - Náhrada škody v případě neprodejnosti výrobků obsahující hhc látky a celkový dopad na podnikání jednotlivců - Právo na zadostiučinění v souvislosti s rozhodováním orgánů družstva - Újma způsobená neprodloužením života závažně nemocné osoby
Keywords: E-knihy; Elektronické knihy; Flipbook; Knihy; Masarykova univerzita; Munipress; Čítárna

The Individual in International Law: History and Theory - Sparks, Tom; Peters, Anne (Oxford University Press, 2024)
978-0-19-889891-7
Keywords: Humanisation; Individual; Individualisation; International law; Legal history; Legal theory

UNCITRAL Model Clause on Adjudication - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Confidentiality - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Highly Expedited Arbitration - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Technical Advisers - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL, HCCH, Unidroit Guida giuridica agli strumenti uniformi in materia di contratti commerciali internazionali, con particolare attenzione alle vendite - United Nations; UN Commission on International Trade Law (Giuffre Francis Lefebvre, 2024)
Keywords: Hague Principles on Choice of Law in International Commercial Contracts; International sale of goods; UN Commission on International Trade Law; UN Convention on Contracts for the International Sale of Goods (1980); UNIDROIT Principles of International Commercial Contracts (2016)